Hybrid bridge structures made of FRP composite and concrete = Mostowe konstrukcje zespolone typu ?kompozyt FRP - beton? - Rajchel, Mateusz; Siwowski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Despite many advantages over the conventional construction materials, the contemporary development of FRP composites in bridge engineering is limited due to high initial cost, low stiffness (in case of glass fibers) and sudden composite failure mode.
Keywords: FRP composite; concrete; hybrid structures; bridges; shaping; kompozyt FRP; beton; konstrukcja zespolona; most; kształtowanie